ANÁLISE DA AÇÃO DO RANELATO DE ESTRÔNCIO EM MODELO EXPERIMENTAL DE OSTEOARTRITE EM RATO. - RODRIGUES, Thiago Alves (2018)
Osteoarthritis (OA) is a multifactorial disease involving diarthrosis, characterized by cellular stress and degradation of the extracellular matrix, associated with micro and macrolesions, that activate maladaptive repair responses. Strontium ranelate (SrRan) has the potential to interfere with the progression of OA. The aim of this experiment was to test the prophylactic and therapeutic effects of the use of SrRan on knee OA. At the first moment of the research, an experimental protocol with induction of knee OA was performed by intra-articular injection of sodium monoiodoacetate. Thirty Wistar rats were divided into five groups with six animals: control group, without interventions; group which received prophylactically SrRan at a daily oral dose of 25 m g/kg for 28 days before induction of OA; groups treated with 25 or 50 mg/kg/day for 28 days after induction; and a group receiving saline after induction. Clinical parameters of pain, (joint incapacity, mechanical hyperalgesia and motor activity) were asse ssed at days zero, seven, 14, 21 and 28 after induction. In the second phase of the research, 30 Wistar rats were distributed in groups similar to the first one, now receiving higher doses of SrRan: the prophylactic group received daily dose of 250 mg/kg for 28 days before induction; and the treated groups received doses of 250 or 500 mg/kg/day for 28 days after induction of OA; besides the control group and the saline group. Behavioral tests, histological evaluation and dosage of synovial inflammatory cytokines (IL-6, IL-10, TNF-α and INF-γ) were performed. The use of smaller doses of SrRan did not promote analgesia in the model studied. As doses increased, an improvement in joint discomfort was observed, both with prophylactic and therapeutic use. The prophylactic use and doses of 500 mg/kg/day also showed improvement of mechanical hyperalgesia. IL-6, IL-10, TNF-α and IFN-γ dosages and histopathological evaluation for the groups receiving SrRan and the control group showed similar means. This work described a possible protective effect of SrRan, both prophylactic and therapeutic, on the articular cartilage, probably associated with an anti-inflammatory action of the drug, with beneficial effect in clinical and morphological parameters in experimental model of OA in rats.